Rancang Bangun Aplikasi Operation Service Mesin Elektronik Data Capture Bank Negara Indonesia Berbasis Web - Mohamad Reza Alfiansyah; Samuel Ramos; Iskandar Zulkarnain (Eksplorasi Teknologi Enterprise & Sistem Informasi (EKSTENSI), 2023)
Bank Negara Indonesia has been established as the oldest recorded commercial bank in the history of the Republic of Indonesia and was formed as the central bank on July 5, 1949. Within the BNI banking system, there is management of Electronic Data Capture (EDC) machines that support service operations. However, the system is still partially computerized and utilizes applications like Microsoft Excel. The current issue faced is the occurrence of inaccurate data and insufficient monitoring of the ongoing data when using the existing system. To address this, this research aims to develop a system by implementing the Unified Modeling Language (UML) as the system modeling method. The system will be built using PHP, a web-based programming language, and MySQL, a relational database management system, which operates on a client-server model.